Intelligent personal assistant concept in context of fault analysis - Cichocki, Piotr; Pokojski, Jerzy (Computer Assisted Methods in Engineering and Science; Vol 14 No 4 (2007), 2022)
The authors of the paper took up Aoyama's [2-6] concept of the integrated industrial processes intent analysis and linked it with the ideas of the designer's IPA (Intelligent Personal Assistant) [23-26]. In many cases it is not sufficient to analyze the engineer's intent depot when trying to explain the origin of a fault. Often computer models are built or real experiments are done with which the considered classes of problems can be analyzed better. The IPA concept was expanded for the process of building computer models and stands for the fault analysis.